PERANAN PUBLIC AREA DI HARRIS RESIDENCES RIVERVIEW KUTA BALI - Putri, Ida Ayu Karina; Sumerta, I Ketut Eli; mahardjono (HARMONY HOSPITALITY, 2022)
This research has background problems including, lack of linen when occoupancy is high, cleaning tools that are not functioning properly are still used in operations, deviations from work procedures by room attendants, lack of time accuracy in cleaning rooms. Therefore, the author raised the title of research on the Role of Supervisor in Improving the Quality of Room Attendant Work at Hotel U Paasha Seminyak Bali. The method used is descriptive qualitative while the research objectives are to determine the role of supervisors in improving the quality of room attendant work, to find out the constraints as supervisor in improving the quality of room attendant work, to find out the supervisor's efforts in overcoming these obstacles in improving the quality of room attendant work at U Paasha Seminyak Bali. The results of this study are supervisors must replace tools that are not functioning properly, in order to get maximum results. To improve the work discipline of subordinates, supervisors must provide their subordinates with a request schedule so that subordinates can be disciplined in their work. Obtained from primary data and secondary data. Using research instruments to improve research results. Data collection techniques by means of observation, interviews and documentation. Also using data analysis techniques. The technique of presenting the results of the analysis where the presentation of the results of this analysis aims to fully clarify what can be obtained at the hotel.